2021
DOI: 10.1002/cncr.33421
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment for distant metastasis in differentiated thyroid cancer using molecular profiling: A matched case‐control study

Abstract: Background Risk stratification for patients with differentiated thyroid cancer (DTC) is based primarily on pathologic tumor characteristics. Accurate preoperative prognostication could allow for more informed initial surgical recommendations, particularly among patients at a higher risk for distant metastasis (DM). The objective of this study was to characterize the genetic profile of DTC with DM and to validate a molecular‐based risk stratification. Methods A case‐control study design was used to analyze pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 28 publications
0
33
0
Order By: Relevance
“…However, most studies have attempted only to determine FTC patients with high metastatic risk 8,9 and poorer outcomes 4,5,10 . Very few studies have focused on how to stratify FTC patients with low metastatic risk 11 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most studies have attempted only to determine FTC patients with high metastatic risk 8,9 and poorer outcomes 4,5,10 . Very few studies have focused on how to stratify FTC patients with low metastatic risk 11 …”
Section: Introductionmentioning
confidence: 99%
“… 4 , 5 , 10 Very few studies have focused on how to stratify FTC patients with low metastatic risk. 11 …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, particularly for aggressive cancers, these data may improve treatment decision-making by informing the triage and extent of surgery only for prognostic markers (39), radioactive iodine administration, and for setting the frequency of follow-up, according to recurrence risk stratification by current criteria most likely complemented by mutations or gene expression classifiers (84). This has been shown in practice, with a recent matched case-control study showing accurate risk stratification of distant metastasis risk by molecular risk groups (76). Simpler methods for identifying prognostic biomarkers may be more efficient than use of a commercially available gene panel, such as single-gene sequencing of TERT or similar targeted approaches, particularly when some genomic information is already available which lessens the incremental value of a large gene panel.…”
Section: Uses Other Than Diagnosismentioning
confidence: 89%
“…Therefore, further longitudinal studies would be required to assess long-term oncological behavior associated with each of these mutations. Song et al [ 44 ] and Yip et al [ 41 ] displayed, respectively, higher recurrence rates and higher 5-year risk of distant metastasis with isolated BRAF V600E -positive tumors. Also, we chose to compare only patients with documented BRAF V600E and RAS -like mutations, thereby introducing a selection bias.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, treatment planning, including choice of surveillance and the appropriate extent of thyroid surgery (i.e., hemithyroidectomy versus total thyroidectomy and prophylactic central neck dissection) and staging of thyroid cancer often heavily rely on tumor size [37]. However, over the past few years, multiple major studies have suggested a progressive shift towards a new pathological classification of thyroid lesions, accounting for genotypic differences and consideration of individualized management depending on mutational profile [39][40][41]. Our findings indeed support this point of view, in regard to the current role and interpretation of tumor size in the management of thyroid nodules.…”
Section: Discussionmentioning
confidence: 99%